Morphology and taxonomy of the orb-weaving spider genus Mecynogea, and a peculiar species of Argiope (Araneae, Araneidae) - Martins, Pedro H.; Santos, Adalberto J. (Zootaxa, 2018)
The spider genus Mecynogea comprises nine species distributed predominantly in the Neotropics. Although the genus has been revised recently, several aspects of its taxonomy and morphology are still unresolved. In this paper, Mecynogea infelix (Soares & Camargo, 1948) is removed from the synonymy of Mecynogea bigibba Simon, 1903 and redescribed. Mecynogea chavona Levi, 1997 is considered a junior synonym of M. infelix. The male of Mecynogea buique Levi, 1997 is described and illustrated for the first time. The internal female genitalia of M. buique and M. infelix is described and shown to be remarkably different from each other. We show that part of the intraspecific variation reported previously for the female of M. infelix is the result of epigynum mutilation, possibly during copulation. We also report the presence of an internal branch on the terminal apophysis in the male palp of Mecynogea species. This structure, in some species visible only on the expanded bulb, is shown to be present in all Cyrtophorinae. The internal branch of the terminal apophysis, together with the conductor fully fused to the tegulum, is herein proposed as synapomorphic for the subfamily. Mecynogea lemniscata (Walckenaer, 1841) is recorded for the first time in Bolivia. We also provide new Brazilian records for M. infelix, M. bigibba, M. buique, M. eryhtromela (Holmberg, 1876), and M. sucre Levi, 1997. Mecynogea carvalhoi Mello-Leitão, 1944, currently considered a nomen dubium, is revalidated, transferred to Argiope Audouin, 1826, redescribed and illustrated for the first time.